Perceptions of a Primary Nursing Care Model in a Pediatric Hematology/Oncology Unit. (January 2017) - Nadeau, Katie; Pinner, Kerri; Murphy, Katie; Belderson, Kristin M.
The primary nursing care model optimizes relationship-based care. Despite using a primary nursing model on a pediatric hematology/oncology inpatient unit, it was hypothesized patients and nurses were dissatisfied with the structure of primary care teams and inconsistency of primary assignments. The purpose of this study was to evaluate patient/family and nurse perceptions of our current care model through assessing gaps in its operationalization and satisfaction. This study used a descriptive cross-sectional design featuring patient/family and nurse surveys. Of the 59 patient/family respondents, 93.2% prefer to have a primary nurse care for them and 85% are satisfied with how often they are assigned a primary care team member. Similarly, 63% of the 57 nurse respondents are satisfied with the current implementation of our primary nursing model and 61% state the model reflects good continuity of care. Yet 80.7% of nurses believe safety would improve for a patient whose nurse works shifts consecutively even if not a primary nurse. Overall, patients, families, and nurses value care continuity and meaningful nurse–patient relationships, which is fundamental to primary nursing.